Latvian un ‘andʼ – loanword or inherited word? - Kabašinskaitė, Birutė; Klingenschmitt, Gert (Baltistica, 2016)
The article deals with the origin of Lat. un ‘andʼ which is generally regarded as a loanword from German und ‘andʼ. As an alternative explanation it offers an interpretation of un as indigenous element of the language. If derived from *u + na (*na being an adverb belonging to the pronominal stem IE *nó ‘thisʼ, cf. Sl. in, earlier ino ‘andʼ < *e + na beside í ‘andʼ < *e of the Slavic sister languages) the formation of un would be paralleled by that of OInd. utá ‘andʼ (Av. uta, OPers. utā < Proto-Iranian *uta) < *u+tá (*-tá < *té or *to belonging to IE *tó- ‘thisʼ). If this interpretation is correct one would be compelled to explain the spelling unde, und used in the Latvian texts of the 16th and 17th centuries as an artificial transformation by the German authors of these texts who were not quite familiar with Latvian and applied the orthography of German to their Latvian texts.